2022
DOI: 10.3390/jcm11123349
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Acute Kidney Injury Epidemiology during the COVID-19 Pandemic: A Retrospective Cohort Study

Abstract: To evaluate the impact of the Coronavirus Disease-19 (COVID-19) pandemic on the epidemiology of acute kidney injury (AKI) in hospitalized patients, we performed a retrospective cohort study comparing data of patients hospitalized from January 2016 to December 2019 (pre-COVID-19 period) and from January to December 2020 (COVID-19 period, including both severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)-negative and positive patients). AKI was classified by evaluating the kinetics of creatinine levels.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Progression and longer duration of AKI in patients with Covid-19 was widely reported in different centers worldwide 17,18,22,24,25 . Likewise, severity of respiratory failure, multiorgan involvement, mechanical ventilation, and ICU admission were consistent ndings among patients who progressed to AKI stage 3 3,17−19 .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Progression and longer duration of AKI in patients with Covid-19 was widely reported in different centers worldwide 17,18,22,24,25 . Likewise, severity of respiratory failure, multiorgan involvement, mechanical ventilation, and ICU admission were consistent ndings among patients who progressed to AKI stage 3 3,17−19 .…”
Section: Discussionmentioning
confidence: 94%
“…Acute Kidney Injury is one of the most common complications of Covid-19 and it has been associated with increased risk of death, prolonged stay in hospital, and need for RRT 2,3,14 . Although age, male sex, and previous uncontrolled comorbidities, such as cardiovascular disease, diabetes and CKD, have been independently associated with worst outcomes among patients with Covid-19 and AKI, few of them are relatively modi able during hospitalization that could improve prognosis 7,[14][15][16][17][18][19][20][21][22][23][24][25][26] . Likewise, data from previous studies have only focused on clinical and biochemical characteristics and have not widely analyzed patient's volume status in non-acute heart failure context and/or previously treated with RRT 6,15,27 .…”
Section: Discussionmentioning
confidence: 99%
“…3 This is particularly crucial because clinical experience and publications have shown that kidney involvement was found up to 75% of the patients with COVID-19. 4 Similarly, obese, elderly and liver compromised patients with COVID-19 are in increased risk of hospitalization/ICU admission. Also, liver injury and abnormal liver function reported in nearly onefourth to half of the hospitalized patients or patients recovered from COVID-19.…”
Section: Fatality and Catastrophe Investigationmentioning
confidence: 99%
“…[3] is is particularly crucial because clinical experience and publications have shown that kidney involvement was found in up to 75% of the patients with COVID-19. [4] Similarly, obese, elderly, and liver compromised patients with COVID-19 are at increased risk of hospitalization/ICU admission. Furthermore, liver injury and abnormal liver function were reported in nearly one-fourth to half of the hospitalized patients or patients who recovered from COVID-19.…”
mentioning
confidence: 99%